2011
DOI: 10.1016/j.neuroscience.2011.02.054
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between the effects of three potential scar-reducing agents applied at a site of sciatic nerve repair

Abstract: We have investigated the effect of three potential scar-reducing agents applied at a sciatic nerve repair site in C57-black-6 mice. Under anaesthesia the nerve was transected, repaired using four epineurial sutures, and 100 mu l of either triamcinolone acetonide (1 mg/100 mu l), an interleukin-10 peptide fragment: (125 ng/100 mu l or 500 ng/100 mu l) or mannose-6-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
1
12
1
Order By: Relevance
“…This present histomorphometric study did not reveal any difference between the repaired nerves treated with the scar‐reducing agent M6P or the PBS placebo. As the results of our previous electrophysiological studies have shown that M6P treatment can enhance nerve regeneration (Ngeow et al. 2011a,b), we hypothesised that we would see an increase in the number and/or size of the myelinated axons distal to the repair site.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…This present histomorphometric study did not reveal any difference between the repaired nerves treated with the scar‐reducing agent M6P or the PBS placebo. As the results of our previous electrophysiological studies have shown that M6P treatment can enhance nerve regeneration (Ngeow et al. 2011a,b), we hypothesised that we would see an increase in the number and/or size of the myelinated axons distal to the repair site.…”
Section: Discussionmentioning
confidence: 97%
“…The remaining solution (80 μL) was then injected between the nerve ends and into the muscle and soft tissues surrounding the repair, and the surgical site closed. A single dose of analgesic was administered (0.01 mL buprenorphine hydrochloride 0.3 mg mL −1 ; Vetergesic ® , Alstoe Animal Health, UK) subcutaneously, and the mice were allowed to recover for 6 weeks; this recovery period was chosen to be the same as used in our previous electrophysiological studies where M6P was shown to have enhanced regeneration (Ngeow et al. 2011a,b).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,11,[16][17][18][19][20] This model is useful for testing the efficacy of new therapies for accelerating and enhancing axon growth and regeneration after injury. When compared with other models of peripheral nerve injury, sciatic nerve crush has several advantages, including easy access to the sciatic nerve.…”
Section: Discussionmentioning
confidence: 99%